Ruptured Cystic Artery Pseudoaneurysm Successfully Treated with Urgent Cholecystectomy: A Case Report and Literature Review - Fujimoto, Yuji (Am J Case Rep, 2018)
Patient: Male, 90 Final Diagnosis: Ruptured cystic artery pseudoaneurysm Symptoms: Epigastric pain • Fever Medication: — Clinical Procedure: Open cholecystectomy Specialty: Gastroenterology and Hepatology OBJECTIVE: Rare disease BACKGROUND: Cystic artery pseudoaneurysm is rare, and some cases are associated with inflammation of the gallbladder. There is limited information regarding this condition, and the clinical features remain unclear. This report is a case of ruptured cystic artery pseudoaneurysm diagnosed by computed tomography (CT) imaging and treated with urgent cholecystectomy and is supported by a literature review of previous cases. CASE REPORT: A 90-year-old man, who had developed acute cholecystitis due to a gallstone one month previously, was referred to our hospital. He developed fever and epigastric pain while waiting for a scheduled elective cholecystectomy. Laboratory investigations showed elevated markers of inflammation and elevated hepatobiliary enzyme levels. Computed tomography (CT) imaging showed cholecystitis and pseudoaneurysm of the cystic artery. The pseudo-aneurysm had ruptured and was accompanied by the formation of a hematoma within the gallbladder that involved the liver bed. Having made the preoperative diagnosis, an urgent open laparotomy was performed, during which the gallbladder was found to have perforated. The hematoma penetrated into the liver bed. Cholecystectomy was performed, and the pseudoaneurysm of the cystic artery was extirpated. There were no serious postoperative complications. A literature review identified 50 previously reported case of cystic artery pseudoaneurysm. CONCLUSIONS: A case of ruptured cystic artery pseudoaneurysm, successfully treated with urgent cholecystectomy is reported, supported by a literature review of previous cases and characterization of the clinical features of this rare condition.